A Facile Method for the Synthesis of Benzoxazole Based Poly(2,6-pyridinylene benzobisoxazole) - Chen, Fenggui; Xu, Yuanjian (Asian Journal of Chemistry, 2015)
In the present study, a novel benzoxazole based rigid rod polymer poly(2,6-pyridinylene benzobisoxazole) containing pyridine unit was synthesized via polycondensation of 4,6-diaminoresorcinol-2,6-pyridinedicarboxylic acid salt monomer, which contains an equal number of moles of 4,6-diaminoresorcinol and 2,6-pyridinedicarboxylic acid structure. The obtained polymer was characterized by FTIR, elementary analysis, X-ray diffraction and themogravimetric analysis. The results showed that poly(2,6-pyridinylene benzobisoxazole) has an excellent thermal stability.